CCR4 Antagonist (C021) Administration Diminishes Hypersensitivity and Enhances the Analgesic Potency of Morphine and Buprenorphine in a Mouse Model of Neuropathic Pain - Bogacka, Joanna; Ciapała, Katarzyna; Pawlik, Katarzyna; Kwiatkowski, Klaudia; Dobrogowski, Jan; Przeklasa-Muszynska, Anna; Mika, Joanna (Frontiers in Immunology, 2020)
Neuropathic pain is a chronic condition that remains a major clinical problem due to high resistance to available therapy. Recent studies have indicated that chemokine signaling pathways are crucial in the development of painful neuropathy; however, the involvement of CC chemokine receptor 4 (CCR4) has not been fully elucidated thus far. Therefore, the aim of our research was to investigate the role of CCR4 in the development of tactile and thermal hypersensitivity, the effectiveness of morphine/buprenorphine and opioid-induced tolerance in mice exposed to chronic constriction injury (CCI) of the sciatic nerve. The results of our research demonstrated that a single intrathecal or intraperitoneal administration of C021, a CCR4 antagonist, dose-dependently diminished neuropathic pain-related behaviors in CCI-exposed mice. After sciatic nerve injury, the spinal expression of CCL17 and CCL22 remained unchanged in contrast to that of CCL2, which was significantly upregulated until day 14 after CCI. Importantly, our results provide evidence that in naive mice, CCL2 may evoke pain-related behaviors through CCR4 since its pronociceptive effects are diminished by C021. In CCI-exposed mice, the pharmacological blockade of CCR4 enhanced the analgesic properties of morphine/buprenorphine and delayed the development of morphine-induced tolerance, which was associated with the silencing of IBA-1 activation in cells and decreases in CCL2 production. The obtained data suggest that the pharmacological blockade of CCR4 may be a new potential therapeutic target for neuropathic pain polytherapy.